Lectin-Glycan Interactions in Corneal Infection and Inflammation - AbuSamra, Dina B.; Argüeso, Pablo (Frontiers in Immunology, 2018)
The cornea is an extraordinary component of vision that functions as the principal barrier to pathogens in the eye while allowing light transmission into the retina. Understanding the cellular and molecular mechanisms that maintain homeostasis in this tissue is the subject of intense scientific study given the high prevalence of corneal disease. Over the past decade, the interactions between lectins and glycans on plasma membranes have emerged as important regulatory factors in corneal biology. In particular, members of the galectin family have been shown to bind multiple β-galactoside-containing receptors to regulate immunopathological processes associated with viral and bacterial infection, transplantation, wound healing, dry eye, angiogenesis and lymphangiogenesis. In this review, we describe the current understanding of how these surface interactions intersect with different pathways to activate unique cellular responses in cornea as well as their potential therapeutic implications.